2022
DOI: 10.3390/molecules27103073
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Evaluation of Ursane-Type Pentacyclic Triterpenoids: β-Boswellic Acid Interferes with the Glycosylation and Transport of Intercellular Adhesion Molecule-1 in Human Lung Adenocarcinoma A549 Cells

Abstract: Ursane-type pentacyclic triterpenoids exert various biological effects, including anticancer and anti-inflammatory activities. We previously reported that ursolic acid, corosolic acid, and asiatic acid interfered with the intracellular trafficking and glycosylation of intercellular adhesion molecule-1 (ICAM-1) in human lung adenocarcinoma A549 cells stimulated with the pro-inflammatory cytokine interleukin-1α. However, the structure–activity relationship of ursane-type pentacyclic triterpenoids remains unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, the molecular mechanisms by which ursolic acid and asiatic acid interfere with protein trafficking from the ER to the Golgi apparatus remain unclear. It was demonstrated that ursane-type β-boswellic acid, a structural isomer of α-boswellic acid (7), induced the accumulation of a shorter ICAM-1 protein, which conjugated to both Endo-H-sensitive and Endo-H-resistant N-glycans in a manner that differed from that of other ursane-type triterpenoids [27]. Therefore, further experiments are needed to identify the target proteins of oleanane-and ursane-type triterpenoids, which may be involved in protein trafficking in the ER to the Golgi apparatus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the molecular mechanisms by which ursolic acid and asiatic acid interfere with protein trafficking from the ER to the Golgi apparatus remain unclear. It was demonstrated that ursane-type β-boswellic acid, a structural isomer of α-boswellic acid (7), induced the accumulation of a shorter ICAM-1 protein, which conjugated to both Endo-H-sensitive and Endo-H-resistant N-glycans in a manner that differed from that of other ursane-type triterpenoids [27]. Therefore, further experiments are needed to identify the target proteins of oleanane-and ursane-type triterpenoids, which may be involved in protein trafficking in the ER to the Golgi apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to ursolic acid, oleanolic acid ( 1 ) and betulinic acid interfered with the N -glycosylation of the ICAM-1 protein but did not markedly prevent its cell surface expression [ 25 ]. The structure–activity relationship of seven ursane-type triterpenoids showed that their inhibitory activities toward the cell surface expression and N -glycosylation of ICAM-1 were affected by the number of hydroxyl groups and/or the presence and position of a carboxyl group [ 27 ]. However, the structure–activity relationship of oleanane-type triterpenoids currently remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ursolic acid significantly reduces intercellular adhesion molecule‐1 cell surface expression, which is linked to pro‐inflammatory cytokines. This function of ursolic acid is related to the presence of carboxyl functional groups and the quantity of hydroxyl functional groups (Nakano et al., 2022).…”
Section: Active Ingredients and Its Action Mechanisms In Six Woody Oi...mentioning
confidence: 99%